Pengaruh Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan (Studi Kasus Pada Perusahaan Semen dan Beton di Bursa Efek Indonesia Tahun 2018-2022) - Lara Fitri Maharani; Murniati (CV. ITTC INDONESIA, 2024)
Disclosure of Corporate Social Responsibilty (CSR) on the financial performance of cement and concrete companies listed on the Indonesia Stock Exchange (BEI). Thesis of Bachelor of Accounting Program Faculty of Economics and Business Univeristas Dharma Andalas. Mentored by mother Murniati's guidance lecturer, SE, MM, Ak, CSRA. This study aims to find out how Corporate Social Responsibility (CSR) influences financial performance in cement and concrete companies listed on Indonesia Stock Exchange (BEI). The type of research used in this study is descriptive quantitative. The data analysis techniques used in this study are financial ratio analysis and simple regression analysis. Based on the results of the analysis, it can be concluded that Corporate Social Responsibility (CSR) does not affect the financial performance measured using Return on Equity (ROE). This means the high and low disclosure of CSR does not affect Return on Equity (ROE). Corporate Social Responsibility (CSR) has no influence on financial performance measured using Return on Assets (ROA). This means that the high and low disclosure of social responsibility does not have any influence on the profitability of the company. Corporate Social Responsibility (CSR) influences financial performance as measured using Earning Per Share (EPS). This means that the higher the disclosure of social responsibility the higher is also the EPS of the company. Increasingly broad disclosure will give a positive signal to interested parties in the company